The Emergence of the Romantic Self in John Ashbery’s Postmodern Poetry - Zahra Eesa (آداب الكوفة)
John Ashbery (1927-2017) is one of the most controversial postmodern poets in America. His work often represents the new modes of expression in the postmodern society; a distorted language and an interest in the ordinary experience of everyday life. His concern is not solely finding a way through language to communicate thoughts, his work rather shows a longing to the past romantic subjectivity which presents a more solid ground for the self in opposition to the fluidity of the postmodern self. In looking for consistency in the experiences of the self while giving importance to the performative quality of language, Ashbery undertakes a reproduction of the old romantic self in postmodern terms. Ashbery’s poems attempt to reveal the experience of the subjective self as it unfolds but without a closure which is a postmodern quality.